Multi-spectral nephelometer characterization of urban aerosols. (15th March 2020) - Devara, P.C.S.; Vijayakumar, K.; Safai, P.D.
Abstract: Latest developments in science and technology enabled the research community to device numerous methods for real-time monitoring and analysis of aerosol properties. Different types of atmospheric aerosols, originating from both natural and anthropogenic sources, interfere with both incoming and out-going solar radiation and cause changes in weather and climate. The presence of these aerosols over any location is due to a combination of local sources and long-range transport which can result in a variety of mixing (both internal and external) states, mainly because of aging and interaction among diverse types of aerosols. These aerosols directly or indirectly interact with solar radiation and influence the lifetime and albedo of clouds and hence precipitation (Intergovernmental Panel on Climate Change (IPCC), 2007). Added, through their scattering and absorption properties, aerosol particles also affect visibility, air quality (Horvath, 1995), and human health (Brunekreef and Holgate, 2002, Balakrishnan et al., 2012, Nadadur et al., 2015). Highlights: Characterization of urban aerosols over a complex terrain. Nephelometer inversion of TSP, PM2.5 and PM10 mass concentrations. Influence of celebrations on atmospheric visibility. Impact of local meteorology on scattering coefficient variations. Air quality from scattering coefficients on weekdays and weekends.